Analisis Dividend Stickiness dan Free Cash Flow terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi - Arief Rio Maulana; Iin Rahmawati; Faradina Inda Wardhani (CV Edujavare Publishing, 2026)
This study examines the impact of dividend stickiness and free cash flow on firm value, with profitability as a moderating variable. Firm value represents an issuer's success in managing shareholder wealth, yet the interaction between cash management and dividend stability remains complex. The research utilizes a quantitative approach analyzing secondary data from 20 constituent companies of the LQ45 index listed on the Indonesia Stock Exchange from 2022 to 2024, resulting in 60 observations. Data were evaluated using panel data regression and Moderated Regression Analysis (MRA) under the Random Effects Model (REM). The findings indicate that dividend stickiness has no significant effect on firm value, suggesting that investors do not prioritize historical dividend stability. Conversely, free cash flow has a strong, significant positive effect on firm value, demonstrating that abundant free cash is perceived as a positive signal of financial flexibility. Furthermore, profitability fails to moderate the effects of both dividend stickiness and free cash flow on firm value. In conclusion, free cash flow is the sole internal catalyst that enhances firm value, as capital market investors rationally evaluate financial signals independently without combining them with current accounting profit fluctuations.